Endoscopic full-thickness plication for the treatment of gastroesophageal reflux after peroral endoscopic myotomy: a randomized sham-controlled study - Maydeo, Amit; Patil, Gaurav; Kamat, Nagesh; Dalal, Ankit; Vadgaonkar, Amol; Parekh, Sanil; Daftary, Rajen; Vora, Sehajad (Endoscopy, 2023)
Background Endoscopic full-thickness plication (EFTP) has shown promising results in gastroesophageal reflux disease (GERD), but its efficacy in GERD after peroral endoscopic myotomy (POEM) is unclear.Methods In a prospective, randomized trial of post-POEM patients dependent on proton pump inhibitors (PPIs) for documented GERD, patients underwent EFTP (plication to remodel the gastroesophageal flap valve) or an endoscopic sham procedure (positioning of the EFTP device, but no stapling). The primary end point was improvement in acid exposure time (AET) < 6 % (3 months). Secondary end points included improvement in esophagitis (3 months), GERD Questionnaire (GERDQ) score (3 and 6 months), and PPI usage (6 months).Results 60 patients were randomized (30 in each group). At 3 months, a significantly higher proportion of patients achieved improvement in AET < 6 % in the EFTP group compared with the sham group (69.0 % [95 %CI 52.1–85.8] vs. 10.3 % [95 %CI 0–21.4], respectively). EFTP was statistically superior to sham (within-group analysis) in improving esophageal AET, DeMeester Score, and all reflux episodes (P < 0.001). A nonsignificant improvement in esophagitis was noted in the EFTP group (P = 0.14). Median GERDQ scores (3 months) were significantly better (P < 0.001) in the EFTP group, and the same trend continued at 6 months. A higher proportion of patients in the sham group continued to use PPIs (72.4 % [95 %CI 56.1–88.7] vs. 27.6 % [95 %CI 11.3–43.8]). There were no major adverse events in either group.Conclusion EFTP improved post-POEM GERD symptoms, 24-hour pH impedance findings with normalization in one-third, and reduced PPI usage at 6 months.